Exploring Students’ Critical Thinking Skills in Geometry through the Context of Betawi Culture: Damdas 3 Batu Game - Utami, Alfida Mukti; Pramudiani, Puri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
One of the demands of 21st century learning is critical thinking. However, nowadays, students' critical thinking skills are still relatively low, particularly in geometry. This research aims to explore students' critical thinking skills through the design of a series of lessons. Realistic Mathematics Education (RME) underlies the design and the context applied. This study was conducted in one of the elementary schools in Jakarta, involving 30 grade IV elementary school students as the research subjects. The method used in this research is descriptive qualitative with an educational ethnographic approach. Data collection techniques involved observation, interviews, and documentation. The results of this study indicate that the implementation of a traditional game-based learning design called Damdas 3 Batu can support students’ critical thinking skills. Through this game, students are able to comprehend the given problems, construct mathematical models adapted to the provided context, solve the problems, and ultimately derive conclusions from the obtained results. Therefore, Damdas 3 Batu can serve as a valuable instructional reference for teaching geometry concepts in elementary schools.